Efficacy of cardioneuroablation for vasodepressor vasovagal syncope - Chen, Zhenhuan; Li, Ying; Liu, Yuan; Shen, Guowang; Xiong, Ganwei; Wu, Bo; Liu, Yanfeng; Huang, Xiantao; Li, Hongyan; Zhou, Haiwen; Xu, Zhicheng; Zhang, Gulao; et al. (Frontiers in Neuroscience, 2025)
ObjectiveCardioneuroablation (CNA) is effective for cardiac inhibitory and mixed vasovagal syncope (VVS) but not for vasodepressor VVS. This study aimed to assess the therapeutic benefits of CNA in vasodepressor VVS.MethodsVVS patients hospitalized in the Department of Cardiology of Jiangxi Provincial People’s Hospital were retrospectively reviewed. Holter monitoring was performed before, during, and 3 months after CNA. Changes in heart rate and atrioventricular conduction before and after ablation were compared.ResultsThirty-five patients (18 M/17F, 47.48 ± 16.49 years) were included. Median duration of syncope was 24.0 months (range, 2.5–66.0). Median number of syncope episodes before treatment was two (range, 2–4). The time domain indexes of heart rate variability, mean heart rate, maximum heart rate, and minimum heart rate were significantly higher 3 months after CNA. Mean follow-up was 11 ± 4.67 months. Recurrent syncope occurred in two patients with vasodepressor VVS, one of them with presyncope symptoms in vasodepressor type; and one patient occurred with mixed VVS, without presyncope symptoms. The syncope free survival is 76.92%. No serious complications occurred. CNA is safe and effective in the treatment of vasodepressor VVS.ConclusionCNA is effective for treating vasodepressor VVS. Our study provides a theoretical basis for individualization of treatment in patients with vasodepressor VVS.